Duchowość w zarządzaniu – wybrane zagadnienia - Sokołowska, Julita (Annales. Etyka w Życiu Gospodarczym, 2012)
The purpose of the article titled „Spirituality in Management” is to outline the area for a more thorough monograph on the problem of the functioning of the spirituality in the organization. The main research question is focused on the use of the elements of spirituality in the management system and how it will improve the efficiency of human labor in organization. In the article are also provided a conceptual framework issues, some lines of analysis of the problem, which can be used in future studies indicating the major benefits associated with the use of spiritual substance in the management and main threats in this area. The nature of research adopted in the article is presented in a form of exploration, which does not have the obligation to adjudge finally all the issues. The form of exploration seems to be in this particular case the appropriate due to the hard-to-describe and irrational nature of selected thematic area (spirituality) and his reference to the sphere, which has not yet been analyzed very often (organization). In the traditional business analyze, derived from economic and management theory of organizational behavior, attention is paid to the concept of prosperity, as the purpose of organizational human functioning. Interpretations of the concept of welfare proposed in the scientific literature, in many cases, are focused mainly on material prosperity. For this reason, care and activity in terms of spiritual well-being are difficult to observe in the lives of professional individuals. However, the negative effects of the elimination of the spiritual element can significantly affect the efficiency of its operation in both spheres – in professional and in private life. In the words of M. Dziewiecki „The more a person is spiritually poor, much less know how to use the material prosperity”. Man does not take account of the spiritual factor in their functioning in the organization and then the organization exposes itself to lower effects by using of resources, and consequently limit the development – waste is the lack of synergy, added value achievable with appropriate use of resources. Material prosperity without spiritual element may lead the individual to self-restraint, self-destruction. Moreover, mental and spiritual poverty of the unit can cause the poverty of the entire social groups.